2001
DOI: 10.1046/j.1528-1157.2001.02700.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Epileptogenesis: Localizing Value of Scalp and Subdural Interictal and Ictal EEG Data

Abstract: Summary:Purpose: To determine the value of scalp epileptiform EEG data and subdural interictal spikes in localizing temporal epileptogenesis among patients requiring invasive recordings. For this delineation, we related such factors to site of subdural seizure origin in 27 consecutive patients.Methods: Patients with temporal lobe epilepsy whose noninvasive lateralizing data were inconclusive and therefore required subdural electroencephalography were studied. All patients had (a) 24-h scalp telemetered EEGs, (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 21 publications
2
25
0
Order By: Relevance
“…Complete lesion resection is the principal determinant of effective surgery (34), but Van Ness et al (35) showed that epileptogenic zone resection also contributes to surgical effectiveness. In a study most relevant to ours, among 31 children with normal or (40) nonspecific neuroimaging, extent of epileptogenic region removal correlated best with effectiveness (36). Lacking a relevant lesion removes a reliable guide to a principal epileptogenic zone, possibly contributing to the bimodal outcomes we encountered (i.e., principally either SF or unhelped; Table 2).…”
Section: Surgical Effectivenessmentioning
confidence: 84%
See 1 more Smart Citation
“…Complete lesion resection is the principal determinant of effective surgery (34), but Van Ness et al (35) showed that epileptogenic zone resection also contributes to surgical effectiveness. In a study most relevant to ours, among 31 children with normal or (40) nonspecific neuroimaging, extent of epileptogenic region removal correlated best with effectiveness (36). Lacking a relevant lesion removes a reliable guide to a principal epileptogenic zone, possibly contributing to the bimodal outcomes we encountered (i.e., principally either SF or unhelped; Table 2).…”
Section: Surgical Effectivenessmentioning
confidence: 84%
“…Among studies that used M 1 , T 1 sphenoidal, or sphenoidal electrodes supplementing the 10-20 system, the site of scalp-recorded seizures in temporal lobe epilepsy correlated with side of invasively recorded seizures or of effective lobectomy in 75-83% of cases (37)(38)(39)(40). Among 67 nonlesional temporal patients rendered SF by surgery, Williamson et al (41) found scalp ictal lateralizing "changes" ultimately appearing in 81% of patients; in 87% of these, the seizures occurred ipsilateral to depth EEG seizures and curative surgery.…”
Section: Scalp Eegmentioning
confidence: 99%
“…A full evaluation for epilepsy may require 24-hour EEG and video monitoring or intracerebral depth electrodes with subdural grid arrays, as these procedures can sometimes identify abnormal electrical discharges not observed on routine EEG. 18,20,21 High resolution magnetic resonance imaging (MRI) is recommended for visualization of the deep temporal lobe structures. 2,22 This is particularly important for reliable separation of the amygdala and hippocampus in order to obtain accurate volume measurements.…”
mentioning
confidence: 99%
“…Non-invasive epileptic source localization techniques, relying on interictal activity in the EEG and mainly motivated by the need for presurgical localization of the epileptic focus in intractable focal epilepsy, have been widely studied and validated (Blume et al, 2001;Ebersole, 2000;Gavaret et al, 2009;Lantz et al, 2003;Michel et al, 2004;Zumsteg et al, 2005Zumsteg et al, , 2006. Source localization methods most often utilize electric source imaging (ESI), a technique which applies various mathematical algorithms and constraining neurophysiological hypotheses on scalp electroencephalographic (EEG) recordings in order to reconstruct the three dimensional brain electrical activity (reviewed in Michel et al, 2004).…”
Section: Introductionmentioning
confidence: 99%